The Follicular Impaction-Nevus Comedonicus - Anubha, Bajaj (International Journal of Sexually Transmitted Diseases, 2020)
Nevus comedonicus (NC) was initially described by Kofmann in1895 and scripted as a “comedo nevus”. Nevus comedonicus  is cogitated as an exceptional subtype of epidermal nevus engendered from the hair follicle and a lesion predisposition for face and neck. Nevus comedonicus syndrome with constituent nevus comedonicus was initially coined by Engber in 1978. Delayed milestones and deferred neonatal development can ensue with nevus comedonicus or nevus comedonicus syndrome12.
Keywords: Nevus comedonicus (NC)